2005
DOI: 10.1016/j.femsle.2005.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia colimediated urinary tract infections: Are there distinct uropathogenicE. coli(UPEC) pathotypes?

Abstract: A variety of virulence genes are associated with Escherichia coli mediated urinary tract infections. Particular sets of virulence factors shared by bacterial strains directing them through a particular pathogenesis process are called a "pathotype." Comparison of co-occurrence of potential urinary tract infection (UTI) virulence genes among different E. coli isolates from fecal and UTI collections provides evidence for multiple pathotypes of uropathogenic E. coli, but current understanding of critical genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(172 citation statements)
references
References 47 publications
4
164
0
4
Order By: Relevance
“…Although Ͻ15% of all commensal E. coli isolates encode genes for HlyA expression, this value is substantially higher among strains that cause cystitis (31-48%), pyelonephritis (44 -49%), or bacteriaemia (39%) (Johnson, 1991;Marrs et al, 2002Marrs et al, , 2005. At high concentrations, HlyA is able to lyse erythrocytes and nucleated host cells, a process that may enable extraintestinal pathogens like UPEC to better cross mucosal barriers, damage effector immune cells, and gain enhanced access to host nutrients and iron stores (Cavalieri et al, 1984;Johnson, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Ͻ15% of all commensal E. coli isolates encode genes for HlyA expression, this value is substantially higher among strains that cause cystitis (31-48%), pyelonephritis (44 -49%), or bacteriaemia (39%) (Johnson, 1991;Marrs et al, 2002Marrs et al, , 2005. At high concentrations, HlyA is able to lyse erythrocytes and nucleated host cells, a process that may enable extraintestinal pathogens like UPEC to better cross mucosal barriers, damage effector immune cells, and gain enhanced access to host nutrients and iron stores (Cavalieri et al, 1984;Johnson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…These data supported the possibility that a secreted factor, common to many UPEC isolates, negatively impacts Akt activation. Two secreted toxins often associated with UPEC strains are cytotoxic necrotizing factor 1 (CNF1) and HlyA (Marrs et al, 2005;Bonacorsi et al, 2006). Targeted disruption of each of these toxin-encoding genes in UTI89 revealed that hlyA, but not cnf1, was required for UTI89-mediated inactivation of Akt ( Figure 2B).…”
Section: Hlya Stimulates Akt Dephosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some strains are pathogenic and cause a wide variety of different intestinal as well as extra-intestinal diseases (Marrs et al, 2005). Extra-intestinal pathogenic E. coli (ExPEC) isolates are a medically significant group of pathogens responsible for significant morbidity, mortality and cost to the healthcare system as a result of urinary tract infections (UTIs), diverse intra-abdominal infections, pneumonia, surgical-site infections, meningitis, osteomyelitis, skin and soft-tissue infections (SSTIs) and bacteraemia (Russo & Johnson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Los genes estudiados se encuentran asociados a cepas de E. coli responsable de infecciones extra-intestinales, considerando el origen de su aislamiento y fueron los siguientes: hly (α-hemolisina), iucC (aerobactina), afa (adhesina afimbrial), fimH (pili tipo 1), neuC (antígeno capsular K1), sfa/foc (pili tipo S y fimbrias tipo 1C), cnf1 (factor necrosante citotóxico), papC (pili tipo P) [23][24][25] , usp (proteína uropatógena específica) 26,27 e ibeA (factor de invasión del endotelio cerebral) 26,27 . Cada gen se estudió en las 146 cepas.…”
Section: Detección De Secuencias Específicas De Genes De Virulencia (Gv)unclassified